Hybrid Approach Combining Off-Pump CABG with Transapical Aortic Valve Implantation via Median Sternotomy - Gotte, J. M.; Rupp, W.; Schild, A.; Horke, A.; Bedda, W.; Doll, N. (The Thoracic and Cardiovascular Surgeon, 2012)
We report the case of a 75-year-old patient diagnosed with severe aortic stenosis and two-vessel coronary artery disease. Due to multiple comorbidities including chronic renal insufficiency, stroke and pulmonary hypertension (EuroSCORE: 34%; STS mortality risk: 14.9%), he was not a candidate for conventional aortic valve surgery. He underwent a novel hybrid treatment approach combining off-pump CABG and transapical aortic valve implantation via a median sternotomy. Extracorporeal circulation could be entirely avoided.
Keywords: aorta/aortic; coronary artery bypass graft surgery, CABG; cardiopulmonary bypass, CPB